Penguatan Kompetensi Petugas Rekam Medis dalam Meningkatkan Kemampuan Clinical Coder Sebagai Upaya Peningkatan Kinerja PMIK di Puskesmas Jatibaru Kota Bima - Uswatun Hasanah; Rizal Pratama Adi Putra; Muhadi Muhadi; Rizal Fikri (STIKES Yayasan RS.Dr.Soetomo, 2026)
Uniformity in writing diagnoses based on medical terminology, in accordance with the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision (ICD-10), is a crucial factor in determining the accuracy of diagnosis codes. Inaccurate use of medical terminology can make it difficult for medical records officers to determine the lead term for a diagnosis, resulting in inaccurate diagnosis codes and implications for the validity of health service data and the accuracy of INA-CBG rates. This activity is a form of Community Service (PKM) aimed at enhancing the competence of medical records officers in understanding medical terminology, disease classification and codification, and coding audits, as an effort to improve clinical coder skills. The methods used were socialization and training, accompanied by coding audit simulations. The activity was carried out at the Jatibaru Community Health Center in Bima City on July 3, 2023, involving five medical records officers. The activity was evaluated through pre-tests and post-tests to measure the increase in participants' understanding. The evaluation results showed an increase in participants' understanding from an average of 60% in the pre-test to 95% in the post-test after participating in the activity. These results indicate that the outreach and training were effective in improving the clinical coding competency of medical records officers. It is hoped that similar activities can be implemented on an ongoing basis to maintain and improve the quality of diagnostic coding and healthcare services in primary healthcare facilities.